Desmoscolecinae from the northern part of the Mocambique Channel (Nematoda, Desmoscolecida) - Decraemer, W. (Bull. Mus. natn. Hist. nat., Paris, 1984)
Locality: Moçambique Channel; Cabinet:
NeMys doc_id: 17002 Locality: Moçambique Channel; Cabinet:; NeMys doc_id: 3790